Role of lncRNAs and circRNAs in Orofacial Clefts - Seelan, Ratnam S.; Greene, Robert M.; Pisano, M. M. (MicroRNA, 2023)
Different modes of gene regulation, such as histone modification, transcription factor binding, DNA methylation, and microRNA (miRNA) expression, are critical for the spatiotemporal expression of genes in developing orofacial tissues. Aberrant regulation in any of these modes may contribute to orofacial defects. Noncoding RNAs (ncRNAs), such as long ncRNAs (lncRNAs) and circular RNAs (circRNAs), have been shown to alter miRNA expression, and are thus emerging as novel contributors to gene regulation. Some of these appear to function as 'miRNA sponges', thereby diminishing the availability of these miRNAs to inhibit the expression of target genes. Such ncRNAs are also termed competitive endogenous RNAs (ceRNAs). Here, we examine emerging data that shed light on how lncRNAs and circRNAs may alter miRNA regulation, thus affecting orofacial development and potentially contributing to orofacial clefting.
Keywords: lncRNA